PROCESSES OF SENESCENCE OF SURFACE LAYERS OF MONOCRISTALIV OF THE GGG IONS NE+ MODIFIED BY IMPLANTATION - Остафійчук, Богдан Костянтинович; Федорів, Василь Дмитрович; Яремій, Іван Петрович; Яремій, С. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The crystalline structure changes, which happened during 3 years in surface layers of GGG single crystals implanted by Не + ions, are studied on the basis of the results of X-ray structural analysis. The strange profiles calculated from experimental diffraction reflection curves are presented. The explanation of mechanisms of origin and relaxation of defects is offered from point of modern ideas about given processes passing on the basis time changes of their parameters.